HYPERDONTIA IN CHILDREN AT THE PAEDIATRIC DENTAL CLINIC: HIPERDONSIA PADA PASIEN KLINIK GIGI ANAK - S.Nagarajan M. P. Sockalingam; Alida Mahyuddin; Wong Ling Siew; Zuryany Mohamed Zahid (Dentika: Dental Journal, 2011)
This was a retrospective study that looked at the prevalence, characteristics, gender predilection and common problems associated with supernumerary teeth found in children at the Paediatric Dental Clinic, National University of Malaysia (UKM). Four hundred ninety clinical records of children with relevant radiographs, mean age of 8 years (range 6-12 yearsold) were analyzed. The result showed that the prevalence of supernumerary teeth was found to be 3.1%. One hundred percent of the supernumerary teeth were found among patients of Mongoloid descendents (Malay and Chinese). Males were more frequently affected than females with a ratio of 4.1:1. Of the 22 supernumerary teeth found, 75.0% of the teeth were unerupted, 91.0% were located at the anterior maxillary region, 77.3% were conical in shape and 72.7% were of mesiodens type. Uneruption of permanent tooth and crowding were the common problems associated with the supernumerary teeth. All patients with supernumerary teeth were in the mixed dentition stage. In conclusion, majority of supernumerary teeth found were unerupted, located at the anterior maxillary region, mesiodens in conical shape and commonly seen in Mongoloid males.